Response to Tinanoff and Palmer: - Joanna M. Douglass, BDS, DDS (2000)
Sugar, notably suaose, is the undisputed dietary etioIogic agent of caries. What remains less apparent is the form and method of consumption that places a preschool child at increased risk of developing early chidhood caries (ECC). As suggested by Tinanoff and Palmer (l), the traditional cause of ECC-inappropriate use of the baby bottle-can no longer be considered the sole etiology. Only half of the papers that examine the relationship between bedtime bottle use and ECC show a significant relationship (2). However, to eIiminate the baby bottle as a cause, or at least a risk marker, for early childhood canes would be premature. In fact, little is known about the behaviors assodated with bottle use that might make it a signrfrcant etiologic factor. Most studies have only asked the question, "Did your child ever go to bed with the bottle?" Few studies have investigated related behaviors, such as whether the child quickly finishes the bottle, whether the child uses the bottle ad lib during the day, or what foodstuff is in the bottIe.